2017
DOI: 10.1902/jop.2017.170042
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Overexpression in Bone Marrow Stromal Cells Promotes Periodontal Regeneration in a Rat Model of Osteoporosis

Abstract: hLEP overexpression in BMSCs can stimulate periodontal regeneration in osteoporotic conditions and might be a promising strategy for periodontal regeneration in patients with osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 50 publications
(57 reference statements)
0
40
0
1
Order By: Relevance
“…The current study provides researchers with a basic, but refine able procedure of how to regenerate tissue. Attempts have already been made to improve the scaffolds with, for example, nano‐particles to enhance osteogenic metabolic activity and thus tissue regeneration, or adding active molecules to the BMSC sheets (e.g., autologous platelet‐rich plasma), or gene transfection (e.g., adenoviruses harboring the human [h]LEP gene) …”
Section: Discussionmentioning
confidence: 99%
“…The current study provides researchers with a basic, but refine able procedure of how to regenerate tissue. Attempts have already been made to improve the scaffolds with, for example, nano‐particles to enhance osteogenic metabolic activity and thus tissue regeneration, or adding active molecules to the BMSC sheets (e.g., autologous platelet‐rich plasma), or gene transfection (e.g., adenoviruses harboring the human [h]LEP gene) …”
Section: Discussionmentioning
confidence: 99%
“…Several studies also demonstrated that a leptin‐deficient mouse model has reduced bone mineral content of long bones, and systemic leptin administration usually exerts a positive effect on bone mass or promoting fracture healing (Reid et al, ; Wu, Shao, Dass, & Wei, ). Leptin deficiency was reported to be associated with increased marrow adipose tissue and reduced bone formation (Lindenmaier et al, ); meanwhile, leptin overexpression promoted the bone differentiation in hBMSCs (Xu, Wu, Zhou, Yang, & Liu, ; Zheng et al, ). Therefore, the balance between APN and leptin secretion, which may also contribute to conflicting results in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Tariq et al (43) found that body weight and body mass index impact BMD, whereas serum leptin is not associated with BMD. Zheng et al (44) identified that LEP overexpression in bone marrow stromal cells can stimulate periodontal regeneration in osteoporotic conditions. The association between LEP and OP is unclear, and should be a focus of future studies.…”
Section: Discussionmentioning
confidence: 99%